Analisis Hukum Terhadap Kewajiban Laporan Keuangan di Pasar Modal: Studi Kasus Manipulasi Laporan Keuangan PT Garuda Indonesia Tahun 2018 - Pridehan, Syahla; Maharani, Velissa; Pane, Elisabet Nauli; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2024)
The financial report of PT Garuda Indonesia (Persero) Tbk in 2019 shook the Indonesian capital market due to the revelation of significant accounting manipulation in its 2018 financial statements. The manipulation involved recognizing unrealized revenue from long-term contracts, rendering the financial reports unreflective of the company's actual financial condition. This practice affected investor confidence, led to a sharp decline in stock prices, and created a negative perception of the company. This research employs a qualitative approach with secondary data analysis, including financial reports, news, and official documentation. The findings reveal that financial manipulation severely impacted the company's reputation and market stability. The Financial Services Authority (OJK) imposed administrative sanctions and ordered a financial statement revision to restore transparency and accountability. This case underscores the importance of compliance with financial reporting standards to maintain market integrity and rebuild investor trust.